Ergonomics and interfaces of traditional information systems: packaging - Paschoarelli, Luis Carlos [UNESP]; Bonfim, Gabriel Henrique Cruz (My University, 2013)
The contemporary world is characterized, among other factors, by the influence of the new computer information systems on the behavior of individuals. However, traditional information systems still have interaction problems with users. The aim of this study was to determine whether the interaction aspects between user versus traditional information systems (particularly the graphics) have been fully studied. To do so, the ergonomic aspects and usability of such systems were reviewed, with emphasis on the problems of visibility, legibility and readability. From that criteria, the evolution of ergonomic studies of information systems was reviewed (bibliometrics technique); and examples of ergonomic and usability problems in packaging were demonstrated (case study). The results confirm that traditional information systems still have problems of interaction between human X system, hindering the effective perception of information.

A contemporaneidade se caracteriza, entre outros fatores, pela influência dos novos sistemas informacionais computacionais no comportamento dos indivíduos. Entretanto, os sistemas informacionais tradicionais ainda apresentam problemas de interação com os usuários. O objetivo deste estudo foi verificar se os aspectos de interação entre usuário versus sistemas informacionais tradicionais (particularmente, os gráficos) já foram plenamente estudados. Para tanto, foram revisados os aspectos ergonômicos e a usabilidade de tais sistemas, com destaque para os problemas de visibilidade, legibilidade e leiturabilidade. A partir desses critérios, foi revisada a evolução dos estudos ergonômicos de sistemas informacionais (técnica de bibliometria); bem com demonstrados exemplos de problemas ergonômicos e de usabilidade em embalagens (estudo de caso). Os resultados confirmam que os sistemas informacionais tradicionais ainda apresentam problemas de interação homem x sistema, o que impede uma efetiva percepção da informação.
Ergonomia e as interfaces de sistemas informacionais tradicionais: embalagens
Keywords: Ergonomics; Information design; Packaging; Ergonomia; Design informacional; Embalagem